Sodium phosphate supplementation and time trial performance in female cyclists - Buck, C. L.; Dawson, B.; Guelfi, K. J.; McNaughton, L.; Wallman, K. E. (Journal of Sports Science & Medicine, 2014)
This study investigated the effects of three doses of sodium phosphate (SP) supplementation on cycling 500 kJ (119.5 Kcal) time trial (TT) performance in female cyclists. Thirteen cyclists participated in a randomised, Latin-square design study where they completed four separate trials after ingesting either a placebo, or one of three different doses (25, 50 or 75 mg.kg-1 fat free mass: FFM) of trisodium phosphate dodecahydrate which was split into four equal doses a day for six days. On the day after the loading phase, the TT was performed on a cycle ergometer. Serum phosphate blood samples were taken at rest both before and after each loading protocol, while a ~21 day washout period separated each loading phase. No significant differences in TT performance were observed between any of the supplementation protocols (p = 0.73) with average completion times for the 25, 50 or 75 mg.kg-1 FFM being, 42:21 ± 07:53, 40:55 ± 07:33 and 40:38 ± 07:20 min respectively, and 40:39 ± 07:51 min for the placebo. Likewise, average and peak power output did not significantly differ between trials (p = 0.06 and p = 0.46, respectively). Consequently, 500 kJ cycling TT performance was not different in any of the supplementation protocols in female cyclists.